2007
DOI: 10.2164/jandrol.106.000752
|View full text |Cite
|
Sign up to set email alerts
|

A Stereological Analysis of the Response of Spermatogenesis to an Acute Inflammatory Episode in Adult Rats

Abstract: Male fertility is inhibited by inflammatory disease, but the mechanisms responsible are poorly defined. The effects of acute systemic inflammation induced by a single IP injection of lipopolysaccharide (LPS) on spermatogenic function in adult male rats were investigated using detailed stereological analysis. The earliest effect observed was a significant maturational delay of meiosis during the leptotene/zygotene phase (at stages IX-XIII) within 24 hours. This was followed within 6 days by an increase in prema… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
56
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(60 citation statements)
references
References 43 publications
4
56
0
Order By: Relevance
“…Sexual hormone alterations are among the side-effects of anti-convulsant drugs (5,25,26). Moreover, the mentioned study showed the reduction level of free testosterone (dihydrotestostrone), Follicle stimulating hormone, luteinized hormone, attaching globulin increase to sexual hormones and level of Estradiol in the users of enzyme infusing drugs.…”
Section: Discussionmentioning
confidence: 93%
“…Sexual hormone alterations are among the side-effects of anti-convulsant drugs (5,25,26). Moreover, the mentioned study showed the reduction level of free testosterone (dihydrotestostrone), Follicle stimulating hormone, luteinized hormone, attaching globulin increase to sexual hormones and level of Estradiol in the users of enzyme infusing drugs.…”
Section: Discussionmentioning
confidence: 93%
“…When acute systemic inflammation is induced by a single sublethal dose of LPS in the rat, the earliest markedly affected manifestation is a significant maturational delay of primary spermatocytes within 24 h; followed by an increase in apoptosis of spermatogonia and early primary spermatocytes within 6 days (Liew et al, 2007). In the LPS-induced acute inflammation model, there is also no detectable apoptosis at earlier time points, but a dramatic increase in the apoptosis of early primary spermatocytes and spermatogonia in the seminiferous epithelium was observed in later periods (Metukuri et al, 2010;O'Bryan et al, 2000).…”
Section: Discussionmentioning
confidence: 99%
“…The precise mechanisms responsible for this inhibition remain unclear and are probably multifactorial, i.e., infection (Adamopoulos et al, 1978;Buch and Havlovec, 1991), inflammation (Hedger, 2011;Kajihara et al, 2006;Liew et al, 2007;O'Bryan et al, 2000), reactive oxygen species (Aly et al, 2012;Gavazza and Catala, 2003;Reddy et al, 2006), proinflammatory cytokine release (Gerdprasert et al, 2002;Riccioli et al, 2006), excessive infiltration of inflammatory cells (Gerdprasert et al, 2002;Hedger, 2002;O'Bryan et al, 2000), and necrotic cell death and apoptosis (Metukuri et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Inflammation can affect the normal function of Leydig cells (16). Lipopolysaccharide (LPS) was used to establish a mouse model of inflammation (17) and the testes were collected to investigate the effects of roscovitine on murine testis inflammation.…”
Section: Introductionmentioning
confidence: 99%